Development of Low-Carbon Energy Supply System in Romania - Timilsina, Govinda (World Bank, Washington, DC, 2016)
Despite the declining trends in total energy consumption, greenhouse gas emissions, energy intensity, and emission intensity over the past two decades, Romania still emits more greenhouse gas per unit of output than many other members of the European Union. The country is looking for further greening of its energy supply system to achieve the clean energy and climate change mitigation goals included in the European Unions 2030 target and 2050 Roadmap. Using an energy supply optimization model, TIMES, this study develops energy supply mixes for Romania under a baseline scenario that satisfies the European Unions current energy and climate targets for 2020, a green scenario that satisfies the European Unions 2030 energy and climate targets, and a super green scenario that satisfies the European Unions prospective 2050 energy road map. The study finds that although Romania could achieve the green scenario at a moderate cost, it would be challenging and costly to achieve the super green scenario.